Physical nature of “anomalous” electrons in high current vacuum diodes - Kozhevnikov, Vasily Y.; Kozyrev, Andrey V. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: A fundamental theoretical explanation is given for the fact that in subnanosecond vacuum diodes there exists a group of electrons with kinetic energies much higher than the applied voltage (multiplied by the value of the elementary charge) qUmax. Methods: A mathematical method is used based on the numerical solution of the Vlasov-Poisson differential equations system for one-dimensional vacuum diodes of various designs. Results: It is shown in detail that the so-called "anomalous" electrons appear in the transient time domain characterizing the processes of establishing current flow in vacuum diodes. Conclusion: It has been convincingly shown that the presence of “anomalous” electrons is not associated with either the diode design or the presence of additional current carriers. In vacuum diodes with a subnanosecond leading edge of the voltage pulse, the excess of energy over qUmax can be over 20%.